Learning from the Barbarians? Reflections on Chinese Identity and 'Race' in the Educational Context. Issue 12 (14th October 2016) - Yan, Hektor K.T.
Abstract: This paper takes a reflective look at the notions of identity, 'race' and ethnicity using a few ancient and modern Chinese 'texts'. It begins with an examination of the reforms known as 'adopting the costume of barbarian/foreign people and practicing mounted archery [hufuqishe ]' carried out by King Wuling 武靈王 (in reign 325–299 BCE) in 307 BCE as described in theZhan Guo Ce 戰國策 and theShiji 史記 by Sima Qian 司馬遷 (c.145-c.87 BCE). Its cultural and educational significance is then discussed in order to show how the issues faced by King Wuling are still relevant to the educational scene in the contemporary world. Some recent materials from Hong Kong school textbooks relating to the issues on identity and 'race' are then used to contrast and compare with the approach taken by King Wuling. This study argues that the inability to take a critical stance toward categories such as 'race' (zhongzu ) risks perpetuating dated and ethically questionable mentalities. In addition, the importance of taking into consideration issues pertaining to purpose and evaluation in the context of education is highlighted.